2005
DOI: 10.1159/000089168
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Tract Percutaneous Nephrolithotomy for Large Complete Staghorn Calculi

Abstract: Introduction: The treatment of large complete staghorn calculi requires a sandwich combination of percutaneous nephrolithotomy (PCNL) and shockwave lithotripsy (SWL) or sometimes open surgery. Many urologists hesitate to place more than 2–3 tracts during PCNL because of the belief that this may increase complications. We present data to support multi-tract PCNL for large (surface area >3,000 mm2) complete staghorn calculi. Patients and Methods: From July 1998 to October 2003, 121 renal units (103 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 26 publications
5
66
2
2
Order By: Relevance
“…Although feasible, access to all the calices through a single percutaneous tract is difficult because of the peculiarities of the renal collecting system, therefore, multiple-access PCNL is the mainstay of the treatment conducted by many urologists, for the management of staghorn calculi. 8,9 Multi-tract approach preserve the advantage of offering straight and alternative accesses to the stone with use of large ultrasonic lithotripters for effective fragmentation and high SFRs . Accesses which are not prevented by the potential existence of anatomic anomalies such as malrotated kidney and infundibular stenosis, while the presence of which could make the access through a single percutaneous tract challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Although feasible, access to all the calices through a single percutaneous tract is difficult because of the peculiarities of the renal collecting system, therefore, multiple-access PCNL is the mainstay of the treatment conducted by many urologists, for the management of staghorn calculi. 8,9 Multi-tract approach preserve the advantage of offering straight and alternative accesses to the stone with use of large ultrasonic lithotripters for effective fragmentation and high SFRs . Accesses which are not prevented by the potential existence of anatomic anomalies such as malrotated kidney and infundibular stenosis, while the presence of which could make the access through a single percutaneous tract challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The little tract was believed to reduce the risk of tract-related complications, while it was more time-consuming to remove stones with large burden [12]. The 32-Fr tract with a large nephroscope was always hampered by the narrow infundibulum and a greater torque would increase the risk of laceration to the renal parenchyma and severe bleeding, especially in solitary kidney [2,13]. To strike a balance, a 24-Fr tract was preferred in this series so that the majority of staghorn calculi could be extracted quickly by EMS Lithoclast with a modified nephroscope via the 24-Fr tract.…”
Section: Discussionmentioning
confidence: 99%
“…The debate continues over the use of single-tract versus multiple-tract PCNL in these cases. Some scholars believed that aggressive PCNL monotherapy using multiple tracts was safe and effective [3,4], and should be the first option for massive renal staghorn calculi. However, Manohar et al [5] found that greater blood loss occurred in patients requiring multiple tracts.…”
mentioning
confidence: 99%